Jawaban:
a.
[tex](f + g)(x) = {x}^{2} + 6x + 8 + ( x + 4) = {x}^{2} + 7x + 12[/tex]
b
[tex](f - g)(x) = {x}^{2} + 6x + 8 - ( x + 4) = {x}^{2} + 5x +4[/tex]
c
[tex](f )(x)g(x) = ( {x}^{2} + 6x + 8 ) ( x + 4) = {x}^{3} + 6 {x}^{2} + 8x + {4}^{2} + 24x + 32 = {x}^{3} + {10}^{2} + 32x + 32[/tex]
d
[tex] \frac{ {x}^{2} + 6x + 8 }{x + 4} = \frac{(x + 4)(x + 2)}{x + 4} = x + 2[/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Jawaban:
a.
[tex](f + g)(x) = {x}^{2} + 6x + 8 + ( x + 4) = {x}^{2} + 7x + 12[/tex]
b
[tex](f - g)(x) = {x}^{2} + 6x + 8 - ( x + 4) = {x}^{2} + 5x +4[/tex]
c
[tex](f )(x)g(x) = ( {x}^{2} + 6x + 8 ) ( x + 4) = {x}^{3} + 6 {x}^{2} + 8x + {4}^{2} + 24x + 32 = {x}^{3} + {10}^{2} + 32x + 32[/tex]
d
[tex] \frac{ {x}^{2} + 6x + 8 }{x + 4} = \frac{(x + 4)(x + 2)}{x + 4} = x + 2[/tex]